Safety and Effectiveness of Tailored Hemorrhoidectomy in Outpatients Setting - Tomasicchio, Giovanni; Martines, Gennaro; Lantone, Giuliano; Dibra, Rigers; Trigiante, Giuseppe; De Fazio, Michele; Picciariello, Arcangelo; Altomare, Donato Francesco; Rinaldi, Marcella (Frontiers in Surgery, 2021)
Introduction Single or double prolapsed pile instead of full muco-haemorrhoidal prolapse is a common finding in patients with symptomatic III or IV degree haemorrhoids. For this selected group of patients, symptoms relief could be achieved by managing the single/double prolapsed piles instead of performing traditional haemorrhoidectomy. The aim of this single-centre study was to evaluate the safety and medium-long term effectiveness of an outpatient tailored Milligan-Morgan haemorrhoidectomy performed under local anaesthesia. Material and Methods Clinical records of 202 patients submitted to outpatient tailored MMH, under local anaesthesia and without anal dilation, treated between 2013 and 2020, were retrospectively reviewed using a prospectively maintained database and completed by a telephone interview or outpatient consultation. Post-operative pain score, need of painkillers, post-operative complications and symptoms recurrence, return to working activities and patient grading assessment scale were recorded. Results Thirty-five (17%) out of 202 patients recruited, were lost to the follow-up. One hundred fifty-two and 15 patients underwent a single and double pile haemorrhoidectomy respectively. With regard to postoperative outcomes, VAS decreased from a median value of 4 (IQR 2-6) the day of surgery to 1 (IQR 0-4) on the 10th postoperative day(p<0.001). Sixty-one patients (37%) needed oral pain killers during the first week after surgery. There was no mortality or major postoperative complication. Bleeding requiring hospital readmission was reported in 7 (4%) patients and one patient underwent emergency surgery with no need of blood transfusion. No postoperative urinary retention, anal incontinence or stricture occurred in the series. During the median follow-up of 39 (IQR 12-60) months, 26 patients (16%) reported symptoms recurrence but only six underwent traditional MMH. Recovery to normal activity occurred within a median period of 6 days (IQR 3-10) and the CPGAS (Clinical Patient Grading Assessment Scale) at 1 year after surgery was reported to be a “good deal better”. Conclusion Tailored MMH performed under local anaesthesia in ambulatory setting can be considered a safe and effective technique with high patients’ compliance and satisfaction.